2015
DOI: 10.1186/s13002-015-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study on medicinal plants used by Maonan people in China

Abstract: BackgroundThis paper is based on an ethnobotanical investigation that focused on the traditional medicinal plants used by local Maonan people to treat human diseases in Maonan concentration regions. The Maonan people have relied on traditional medicine since ancient times, especially medicinal plants. The aim of this study is to document medicinal plants used by the Maonans and to report the status of medicinal plants and associated traditional knowledge.MethodsEthnobotanical data were collected from June 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
82
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 26 publications
(23 reference statements)
13
82
1
2
Order By: Relevance
“…Previously, it was reported that Forsythia suspense (Thunb.) Vahl could be used to treat diabetes, but the underlying mechanism is unclear (Hong et al, 2015;Nawash et al, 2013). For this reason, the antidiabetic and antihyperlipidemic activities of F. suspensa were evaluated on STZ-induced diabetic mice in this study with the purpose to understand the underlying rational.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that Forsythia suspense (Thunb.) Vahl could be used to treat diabetes, but the underlying mechanism is unclear (Hong et al, 2015;Nawash et al, 2013). For this reason, the antidiabetic and antihyperlipidemic activities of F. suspensa were evaluated on STZ-induced diabetic mice in this study with the purpose to understand the underlying rational.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, young girls and boys who are precociously involve in marital life displayed good knowledge of medicinal plants used during pregnancy, birth and after birth [59]. In contrast to that, studies undertaken in Ethiopia [69] and China [70] showed an interest loss on the use of medicinal plants among young people caused by the influence of modernization.…”
Section: Discussionmentioning
confidence: 99%
“…This role played by young people facilitated the sharing of knowledge between seniors and the younger generation. In contrast, studies undertaken in Ethiopia and China showed an interest loss on the use of medicinal plants among young people caused by the influence of modernization (Giday et al, 2009;Hong et al, 2015).…”
Section: Discussionmentioning
confidence: 94%